Ascorbyl palmitate effects on the stability of curcumin-loaded soybean phosphatidylcholine liposomes. (June 2021) - Li, Junhua; Chang, Cuihua; Zhai, Jiali; Yang, Yanjun; Yu, Haitao
Abstract: The effect of ascorbyl palmitate (AP) on the physical stability of soy phosphatidylcholine (SPC) liposomes and the retention rate of curcumin loaded into SPC liposomes enriched with different concentrations of AP was studied. Results showed that the transmittance, stability coefficient and particle size of liposomes were all influenced by the addition of AP. The highest stability of AP-stabilized liposomes was achieved when the mass ratio of SPC to AP was at 50:5 by increasing the surface charge, as indicated by an increase in ζ-potential from −15.1 mV (pure liposome) to −35.4 mV (AP-enriched SPC). Beyond this ratio, excessive AP addition was unfavorable to the stability of liposomes. Also at this 10% ratio, small angle X-ray scattering and differential scanning calorimetry results showed the strongest interaction between AP and the SPC liposomes, with the altering of the bilayer structure and the main phase transition temperature. Atomic force microscopy results showed that the addition of AP did not obviously change the vesicle microstructure but increased the vesicle height and contact angle. When curcumin was loaded into AP-enriched liposomes as a model bioactive, the best storage stability was observed in the liposome formulation with 10% added AP, which correlated well with the physical stability of the system. These results open up the possibility of AP-modified liposomes being developed as a multifunctional formulation for encapsulating and delivering nutraceuticals. Graphical abstract: Image 1 Highlights: Appropriate addition of ascorbyl palmitate could improve the stability of liposomes. Ascorbyl palmitate reduced the size of liposomes by increasing surface charge. Presence of ascorbyl palmitate facilitated the formation of rigid liposome structure. Curcumin storage stability in liposomes could be improved using ascorbyl palmitate.